Digital Literacy Education: The Utilization of Information Technology in Social Media Among Students of SMP Negeri 2 Mekar Baru, Tangerang Regency - Ramadhan Ibrahim; Fajar Widianto; Edward Felix Satria Sridana; Jonatan Reky Tasyam; Muhamad Nawawi; Agung Budi Susanto; Winarni (Jurnal Pengabdian Cita Masyarakat, 2026)
The rapid transition towards Society 5.0 exposes adolescents to significant cyber risks, necessitating comprehensive digital literacy education. This community service aimed to enhance digital resilience and ethical social media utilization among students at SMP Negeri 2 Mekar Baru. Utilizing a Participatory Action Research approach combined with experiential learning, the intervention engaged 23 randomly selected students in an interactive workshop. The program uniquely integrated generative artificial intelligence tools, specifically NotebookLM for critical data validation, Pippit AI for ethical visual transformation, and Suno AI for affective musical creation. Results demonstrated a highly significant transformation in student behavior, shifting their paradigm from passive technology consumers to proactive, responsible digital content creators. This integration of advanced technological instruments proved exceptionally effective in building systemic cyber resilience, fostering critical thinking, strengthening data privacy awareness, and preparing youth for complex future digital challenges within modern educational ecosystems to ensure sustainable community empowerment and absolute technological safety.